Capital Market Reaction Analysis Before And After The Implementation Of The Makan Bergizi Gratis (Mbg) Program - Zulfajry Al Syafaat; Tenri S.P. Dipoatmodjo; Annisa Paramaswary Aslam (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study aims to analyze the capital market reaction to the implementation of the Makan Bergizi Gratis (MBG) Program announced by the Indonesian government on January 6, 2025, focusing on food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX). The main research problem is whether there are differences in abnormal return and trading volume activity (TVA) before and after the policy implementation. The study employs an event study method with a comparative approach, using stock closing prices and trading volume data over a 21-day observation period (10 days before and after the event). The sample was selected through purposive sampling, consisting of 54 companies. Data analysis was conducted using the Paired Sample T-Test for normally distributed data. The results show significance values of 0.459 for abnormal return and 0.135 for trading volume activity, both exceeding the 0.05 significance level. This indicates that there is no significant difference before and after the implementation of the MBG program. These findings suggest that the MBG policy did not generate a meaningful market reaction and is perceived as a long-term social policy rather than a direct economic stimulus affecting corporate performance. The results align with the efficient market hypothesis and signaling theory, which posit that markets only respond to events containing strong economic information. Therefore, the MBG policy was not regarded as a significant economic signal by investors during the observation period. Keywords: Abnormal Return; Trading Volume Activity; Makan Bergizi Gratis Program; Event Study; Market Reaction